2019
DOI: 10.5194/hess-23-1035-2019
|View full text |Cite
|
Sign up to set email alerts
|

HESS Opinions: Socio-economic and ecological trade-offs of flood management – benefits of a transdisciplinary approach

Abstract: Abstract. In light of climate change and growing numbers of people inhabiting riverine floodplains, worldwide demand for flood protection is increasing, typically through engineering approaches such as more and bigger levees. However, the well-documented “levee effect” of increased floodplain use following levee construction or enhancement often results in increased problems, especially when levees fail or are compromised by big flood events. Herein, we argue that there are also unintended socio-economic and e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 54 publications
0
36
0
Order By: Relevance
“…Multiple stressors, including environmental and anthropogenic impacts such as climate change, pollution, habitat fragmentation and degradation, contributed to a massive decline in aquatic biodiversity in the last century [1][2][3][4][5]. In this context, especially riverine fish species experience the greatest threat by river regulation and fragmentation due to barriers including weirs, dams and hydroelectric plants [6,7]. The latter can have detrimental consequences for fish populations such as preventing migratory species from moving between key habitats during their life cycles [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple stressors, including environmental and anthropogenic impacts such as climate change, pollution, habitat fragmentation and degradation, contributed to a massive decline in aquatic biodiversity in the last century [1][2][3][4][5]. In this context, especially riverine fish species experience the greatest threat by river regulation and fragmentation due to barriers including weirs, dams and hydroelectric plants [6,7]. The latter can have detrimental consequences for fish populations such as preventing migratory species from moving between key habitats during their life cycles [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, this kind of defence presents several ecological (e.g. hydraulic decoupling between the river and its floodplain, loss of biodiversity, change in groundwater levels, and increase in greenhouse gas emission) and socio-economic consequences (Auerswald et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is relevant to note that high-resolution DTMs can be exploited thanks to the availability of parallel 2-D codes; until a few years ago, traditional 2-D and 1-D-2-D models usually adopted a low resolution of the order of 50-100 m for flood-prone areas in order to reduce the computational times (Aureli and Mignosa, 2004;Aureli et al, 2005;Vorogushyn et al, 2010;Masoero et al, 2013;Mazzoleni et al, 2013;Huthoff et al, 2015).…”
Section: Topographic Data and Spatial Resolutionmentioning
confidence: 99%
“…It is likely that temporally varying connections exist between indices of climate variability and variability of the likelihood of destructive abundance of water. Blöschl et al (2017) noted no "consistent climate change signal in flood magnitudes" in Europe, while Di Baldassarre et al (2010) reported a similar finding for Africa. Blöschl et al (2017) found climate-induced patterns of change in observed flood timing in Europe, at the continental scale.…”
Section: Introductionmentioning
confidence: 99%
“…Blöschl et al (2017) noted no "consistent climate change signal in flood magnitudes" in Europe, while Di Baldassarre et al (2010) reported a similar finding for Africa. Blöschl et al (2017) found climate-induced patterns of change in observed flood timing in Europe, at the continental scale. They detected earlier spring snowmelt floods throughout northeastern Europe (warming-driven change), later winter floods around the North Sea and part of the Mediterranean coast (related to polar warming), and earlier winter floods in western Europe (reflecting advancement of soil moisture maxima).…”
Section: Introductionmentioning
confidence: 99%